The Classical Receptive Field Surround of Primate Parasol Ganglion Cells Is Mediated Primarily by a Non-GABAergic Pathway - McMahon, Matthew J. (J Neurosci, 2004)
Although the center-surround receptive field is a fundamental property of retinal ganglion cells, the circuitry that mediates surround inhibition remains controversial. We examined the contribution of horizontal cells and amacrine cells to the surround of parasol ganglion cells of macaque and baboon retina by measuring receptive field structure before and during the application of drugs that have been shown previously to affect surrounds in a range of mammalian and nonmammalian species. Carbenoxolone and cobalt, thought to attenuate feedback from horizontal cells to cones, severely reduced the surround. Tetrodotoxin, which blocks sodium spiking in amacrine cells, and picrotoxin, which blocks the inhibitory action of GABA, only slightly reduced the surround. These data are consistent with the hypothesis that the surrounds of light-adapted parasol ganglion cells are generated primarily by non-GABAergic horizontal cell feedback in the outer retina, with a small contribution from GABAergic amacrine cells of the inner retina.